Involvement of ribonuclease Y in pilus production by M49 Streptococcus pyogenes strain via modulation of messenger RNA level of transcriptional regulator - Kubota, Seiko; Nakata, Masanobu; Hirose, Yujiro; Yamaguchi, Masaya; Kreikemeyer, Bernd; Uzawa, Narikazu; Sumitomo, Tomoko; Kawabata, Shigetada (Microbiology and immunology, 2023)
Streptococcus pyogenes displays a wide variety of pili, which is largely dependent on serotype. A distinct subset of S. pyogenes strains that possess the Nra transcriptional regulator demonstrates thermoregulated pilus production. Findings obtained in the present study of an Nra-positive serotype M49 strain revealed involvement of conserved virulence factor A (CvfA), also referred to as ribonuclease Y (RNase Y), in virulence factor expression and pilus production, while a cvfA deletion strain showed reduced pilus production and adherence to human keratinocytes as compared with wild-type and revertant strains. Furthermore, transcript levels of pilus subunits and srtC2 genes were decreased by cvfA deletion, which was remarkable at 25°C. Likewise, both messenger RNA (mRNA) and protein levels of Nra were remarkably decreased by cvfA deletion. Whether the expression of other pilus-related regulators, including fasX and CovR, was subject to thermoregulation was also examined. While the mRNA level of fasX, which inhibits cpa and fctA translation, was decreased by cvfA deletion at both 37°C and 25°C, CovR mRNA and protein levels, as well as its phosphorylation level were not significantly changed, suggesting that neither fasX nor CovR is necessarily involved in thermosensitive pilus production. Phenotypic analysis of the mutant strains revealed that culture temperature and cvfA deletion had varied effects on streptolysin S and SpeB activities. Furthermore, bactericidal assay data showed that cvfA deletion decreased the rate of survival in human blood. Together, the present findings indicate that CvfA is involved in regulation of pilus production and virulence-related phenotypes of the serotype M49 strain of S. pyogenes.